Observations of the Interaction and Transport of Fine Mode Aerosols With Cloud and/or Fog in Northeast Asia From Aerosol Robotic Network and Satellite Remote Sensing. Issue 10 (31st May 2018) - Eck, T. F.; Holben, B. N.; Reid, J. S.; Xian, P.; Giles, D. M.; Sinyuk, A.; Smirnov, A.; Schafer, J. S.; Slutsker, I.; Kim, J.; Koo, J.‐H.; Choi, M.; et al.
Abstract: Analysis of Sun photometer measured and satellite retrieved aerosol optical depth (AOD) data has shown that major aerosol pollution events with very high fine mode AOD (>1.0 in midvisible) in the China/Korea/Japan region are often observed to be associated with significant cloud cover. This makes remote sensing of these events difficult even for high temporal resolution Sun photometer measurements. Possible physical mechanisms for these events that have high AOD include a combination of aerosol humidification, cloud processing, and meteorological covariation with atmospheric stability and convergence. The new development of Aerosol Robotic Network Version 3 Level 2 AOD with improved cloud screening algorithms now allow for unprecedented ability to monitor these extreme fine mode pollution events. Further, the spectral deconvolution algorithm (SDA) applied to Level 1 data (L1; no cloud screening) provides an even more comprehensive assessment of fine mode AOD than L2 in current and previous data versions. Studying the 2012 winter‐summer period, comparisons of Aerosol Robotic Network L1 SDA daily average fine mode AOD data showed that Moderate Resolution Imaging Spectroradiometer satellite remote sensing of AOD often did not retrieve and/or identify some of the highest fine mode AOD events in this region. Also, compared to models that include data assimilation of satellite retrieved AOD, the L1 SDA fine mode AOD was significantly higher in magnitude, particularly for the highest AOD events that were often associated with significant cloudiness. Key Points: Major pollution events with high fine mode AOD in Eastern China and South Korea are often associated with significant cloud cover New AERONET Version 3 cloud screening allows more AOD observations in the near‐cloud environment to be raised to Level 2 MODIS satellite retrieval algorithms of AOD (collections 5 and 6.0) often screened out a significant number of high fine mode AOD days